2023
DOI: 10.1108/jibr-03-2021-0113
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and non-performing assets: the role of knowledge assets in improving credit quality of Indian banking sector

Abstract: Purpose Intellectual capital (IC) is beneficial to the improved performance of businesses, irrespective of their industry. The present study proposes to check if the use of IC can also help in improving the asset quality of banks. Thus, this study aims to examine the impact of IC and its components on non-performing assets (NPAs). Design/methodology/approach The study has been conducted with a sample of 30 Indian commercial banks and analysed over a time frame of 15 years (2004–2005 to 2018–2019). The modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 83 publications
0
1
0
Order By: Relevance
“…Integral to this process, microfinance officers' possession of intellectual capital, including knowledge, skills, training, and positive intangible capabilities, proved essential. A study by Gaur & Gupta (2023) indicated that intellectual capital positively influences the management of non-performing assets and aids in the handling of problematic loans, starting from the approval of loan applications. This highlights the holistic approach required in managing the intricate and critical stage of loan processing within microfinancing operations.…”
Section: Loan Processingmentioning
confidence: 99%
“…Integral to this process, microfinance officers' possession of intellectual capital, including knowledge, skills, training, and positive intangible capabilities, proved essential. A study by Gaur & Gupta (2023) indicated that intellectual capital positively influences the management of non-performing assets and aids in the handling of problematic loans, starting from the approval of loan applications. This highlights the holistic approach required in managing the intricate and critical stage of loan processing within microfinancing operations.…”
Section: Loan Processingmentioning
confidence: 99%
“…The researchers specially in the field of management, have conducted the researches on Intellectual Capital in various sectors of India such as banking. pharma, manufacturing, haelthcare, higher education, business process outsourcing, electrician, mining asset financing and services (Gaur and Gupta, 2023; Gupta et al ., 2023; Rani and Sharma, 2023; Dharni and Jameel, 2021; Tiwari, 2022; Chatterji and Kiran, 2021; Raushan and Khan, 2017; Narwal and Yadav, 2017), but Indian sugar mill sector is an unexplored area in the existing literature. The contributions of this paper may be summarized as it is the first analytical research that evaluates the impact of IC on business performance of sugar mill companies in India.…”
Section: Introductionmentioning
confidence: 99%